An Examination of the Application of Law No. 2 of 2012 Regarding Land Procurement for Projects in the Public Interest, Focusing on the Resolution of Land Disputes for the Construction of Kediri Airport - Arifin, Zainal; Puasa Handayani, Emi; Ghani Bayhaqi, Naufal (International Asia Of Law and Money Laundering, 2024)
This research endeavors to address two primary research questions regarding the disputes arising in the land acquisition process for the development of an airport in Kediri. Firstly, it investigates the nature of disputes occurring during the land acquisition process for airport construction in Kediri. Secondly, it examines the resolution of land acquisition disputes for the airport development in Kediri and assesses its conformity with Law Number 2 of 2012. Employing an empirical method with a qualitative approach, this study provides insights into the aforementioned research inquirie. The findings reveal persistent challenges in land acquisition for the airport development in Kediri. The resolution of land disputes in Kediri's Airport development project does not fully adhere to the provisions of Law Number 2 of 2012 concerning land acquisition for public interest development. The mechanism of consensus-building meetings (musyawarah mufakat) proves ineffective due to power imbalances between the airport authorities and the local community. Mediation processes fail to yield agreements due to the unpreparedness of involved parties and the lack of mediator professionalism. Moreover, consignment (konsinyasi) often falls short of being an effective solution as the local community lacks adequate knowledge and comprehensive information regarding the consignment process.